Prognostic value of nonangiogenic and angiogenic growth patterns in non-small-cell lung cancer. - Sardari Nia, P; Colpaert, C; Blyweert, B; Kui, B; Vermeulen, P; Ferguson, M; Hendriks, J; Weyler, J; Pezzella, F; Van Marck, E; Van Schil, P (2004)
An essential prerequisite of nonangiogenic growth appears to be the ability of the tumour to preserve the parenchymal structures of the host tissue. This morphological feature is visible on a routine tissue section. Based on this feature, we classified haematoxylin and eosin-stained tissue sections from 279 patients with non-small-cell lung cancer into three growth patterns: destructive (angiogenic; n=196), papillary (intermediate; n=38) and alveolar (nonangiogenic; n=45). A Cox multiple regression model was used to test the prognostic value of growth patterns together with other relevant clinicopathological factors. For overall survival, growth pattern (P=0.007), N-status (P=0.001), age (P=0.020) and type of operation (P=0.056) were independent prognostic factors. For disease-free survival, only growth pattern (P=0.007) and N-status (P<0.001) had an independent prognostic value. Alveolar (hazard ratio=1.825, 95% confidence interval=1.117-2.980, P=0.016) and papillary (hazard ratio=1.977, 95% confidence interval=1.169-3.345, P=0.011) growth patterns were independent predictors of poor prognosis. The proposed classification has an independent prognostic value for overall survival as well as for disease-free survival, providing a possible explanation for survival differences of patients in the same disease stage.